2018
DOI: 10.1002/adhm.201800812
|View full text |Cite
|
Sign up to set email alerts
|

An Additive to PMMA Bone Cement Enables Postimplantation Drug Refilling, Broadens Range of Compatible Antibiotics, and Prolongs Antimicrobial Therapy

Abstract: Poly(methyl methacrylate) (PMMA) bone cement is used in several biomedical applications including as antibiotic-filled beads, temporary skeletal spacers, and cement for orthopedic implant fixation. To mitigate infection following surgery, antibiotics are often mixed into bone cement to achieve local delivery. However, since implanted cement is often structural, incorporated antibiotics must not compromise mechanical properties; this limits the selection of compatible antibiotics. Furthermore, antibiotics canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
144
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(146 citation statements)
references
References 56 publications
1
144
0
Order By: Relevance
“…However this amount is similar to the amount of RM remaining in non‐templated polymers as determined by colorimetric spectroscopy (data not shown) and FTIR analysis (Figure ). Past work by our lab has shown that any drug remaining in the device was unavailable for further delivery even after extensive washing with organic solvents, so total drug loading was calculated from the maximum released amount, rather than maximum loaded amount …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…However this amount is similar to the amount of RM remaining in non‐templated polymers as determined by colorimetric spectroscopy (data not shown) and FTIR analysis (Figure ). Past work by our lab has shown that any drug remaining in the device was unavailable for further delivery even after extensive washing with organic solvents, so total drug loading was calculated from the maximum released amount, rather than maximum loaded amount …”
Section: Resultsmentioning
confidence: 81%
“…Past work by our lab has shown that any drug remaining in the device was unavailable for further delivery even after extensive washing with organic solvents, so total drug loading was calculated from the maximum released amount, rather than maximum loaded amount. [37,38]…”
Section: Supramolecular Hydrogel Synthesismentioning
confidence: 99%
“…When CD is insolubilized by forming a high molecular weight polymer, we can take advantage of this molecular affinity to alter the rate of release beyond that capable of diffusion alone. Past work from our lab and others has shown that this affinity reduces the initial drug burst effect, retaining more drug to be delivered at later time points . Additionally, loading CD polymers is very straightforward, and can be done post‐polymerization, allowing drug incorporation for dual drug loading and release.…”
Section: Introductionmentioning
confidence: 99%
“…Past work from our lab and others has shown that this affinity reduces the initial drug burst effect, retaining more drug to be delivered at later time points. 41 Additionally, loading CD polymers is very straightforward, and can be done post-polymerization, allowing drug incorporation for dual drug loading and release.…”
Section: Introductionmentioning
confidence: 99%
“…In order to locally deliver antibiotics in orthopedic procedures, such as knee or hip replacements, an antibiotic is often directly added to poly(methyl methacrylate) (PMMA) bone cement during the mixing process 13 . PMMA is used in a variety of orthopedic and non-orthopedic applications including as a temporary spacer in a two-part revision procedure 14 , as an anchor between the patient's bone and the metallic implant in arthroplasties 15 , and as antibiotic-filled beads [16][17] . In these applications, typically only one antibiotic, such as gentamicin or tobramycin, is used in an effort to provide antimicrobial coverage 18 .…”
Section: Introductionmentioning
confidence: 99%